2017
DOI: 10.3346/jkms.2017.32.1.151
|View full text |Cite
|
Sign up to set email alerts
|

Differential Cell Count and CRP Level in Blood as Predictors for Middle East Respiratory Syndrome Coronavirus Infection in Acute Febrile Patients during Nosocomial Outbreak

Abstract: A case-control study was performed to identify clinical predictors for Middle East respiratory syndrome coronavirus (MERS-CoV) infection among patients with acute febrile illness during the nosocomial outbreak. Patients with MERS-CoV were more likely to have monocytosis with normal white blood cell (WBC) count and lower C-reactive protein (CRP) level. Simple laboratory data such as complete blood counts (CBC) with differential count could be a useful marker for the prediction of MERS and triage at the initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 14 publications
1
15
1
Order By: Relevance
“…As seen in Table 2 , more than 80% of the patients exhibited lymphopenia, especially for CD4+ and CD8+ T lymphocytes (91.3%), which confirmed the previous study that SARS-CoV-2 infection damaged the immune system ( Huang et al, 2020a ). Approximately half of the patients exhibited decreased Th/Ts ratios, which differed from Middle East respiratory syndrome( Park et al, 2017 ). C-reactive protein (CRP) was elevated in 85.6% of the patients, and procalcitonin (PCT) was slightly increased.…”
Section: Resultsmentioning
confidence: 99%
“…As seen in Table 2 , more than 80% of the patients exhibited lymphopenia, especially for CD4+ and CD8+ T lymphocytes (91.3%), which confirmed the previous study that SARS-CoV-2 infection damaged the immune system ( Huang et al, 2020a ). Approximately half of the patients exhibited decreased Th/Ts ratios, which differed from Middle East respiratory syndrome( Park et al, 2017 ). C-reactive protein (CRP) was elevated in 85.6% of the patients, and procalcitonin (PCT) was slightly increased.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have suggested that a lymphocyte‐to‐monocyte ratio value <2 is a surrogate indicator for influenza A 12,13 . In addition, increased monocyte and decreased lymphocyte counts were found in patients with Middle East respiratory syndrome coronavirus (MERS‐CoV), indicating the potential predictive value of MLR for MERS 22 . It has been reported that some serum cytokines (IL‐6 and IFN‐α) and chemokines (IL‐8, CXCL‐10, and CCL‐5) are correlated with increased peripheral blood monocytes in patients with MERS, suggesting a possible effect on increasing the MLR 23 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that pneumonia caused by 2009 H1N1 influenza alone had significantly lower C‐reactive protein level than mixed bacterial and viral infection pneumonia 19 . Additionally, patients with Middle East respiratory syndrome coronavirus (MERS‐CoV) also often have lower C‐reactive protein level among patients with acute febrile illness 20 …”
Section: Discussionmentioning
confidence: 99%